2020
DOI: 10.1177/0972150920945687
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Indian Economy: Impact on Growth, Manufacturing, Trade and MSME Sector

Abstract: The study aims to make an assessment of COVID-19 on Indian economy by analysing its impact on growth, manufacturing, trade and micro, small and medium enterprises (MSME) sector, and highlights key policy measures to control the possible fallout in the economy. The impact of the pandemic across sectors and in different scenarios of complete, extended and partial lockdown, and at different levels of capacity utilization is massive on the Indian economy. India’s economy may barely manage to have a positive growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 3 publications
(3 reference statements)
7
127
0
7
Order By: Relevance
“…The investigation of [39] indicated that increases in COVID-19 cases and deaths have imperatively damaged the financial stability, which significantly impacts the manufacturing sector and global economy. The investigation done by [40] revealed that COVID-19 has expressively affected the manufacturing sector worldwide. Particularly, it will shrink the manufacturing sector of India by 5.5% to 20%.…”
Section: Mean Equation Outcomesmentioning
confidence: 99%
“…The investigation of [39] indicated that increases in COVID-19 cases and deaths have imperatively damaged the financial stability, which significantly impacts the manufacturing sector and global economy. The investigation done by [40] revealed that COVID-19 has expressively affected the manufacturing sector worldwide. Particularly, it will shrink the manufacturing sector of India by 5.5% to 20%.…”
Section: Mean Equation Outcomesmentioning
confidence: 99%
“…The unexpected outbreak of novel coronavirus contagion has created an unparalleled and devastating hazard to both human health and the socio-economic prosperity across the globe, and the world is yet confused about its severity and span. It has been observed to work through a highly interdependent world with interconnected production networks and financial markets (Sahoo & Ashwani, 2020). The economic fallouts of this pandemic mainly include a strained healthcare system, disrupted supply chain and trade, and plummeted production, consumption and investment activities.…”
Section: Introductionmentioning
confidence: 99%
“…This means that central and state institutes should put intensive efforts in order to produce quality research in relation to the pandemic (Vasantha Raju & Patil, 2020). But at the same time, there have been important attempts by the Indian researchers to study this phenomenon from various aspects (Behl & Mishra, 2020;Sahoo & Ashwani, 2020…”
Section: Discussionmentioning
confidence: 99%